تحديد نزر بعض العناصر المعدنية الثقيلة في أوراق وساق نبات القصب Avundodonax L.المنتشرة في مدينة اللاذقية باستخدام مطيافية الامتصاص الذري - غندور, وفاء; لايقة, حسام الدين (Latakia University Journal -Biological Sciences Series, 2016)
تهدف هذه الدراسة إلى تحديد نزر بعض العناصر المعدنية الثقيلةpb, Cd, Cu, Zn & Fe في أوراق وساق نبات القصب. جمعت العينات من عشرين موقعاً، وقسمت في أربع مجموعات بحسب الحركة المرورية والأنشطة البشرية، وقد تم تحديد تراكيز العناصر باستخدام مطيافية الامتصاص الذري.أظهرت النتائج ارتفاع تراكيز كل من الرصاص، الكادميوم والنحاس في أوراق وساق القصب مما سمح باستخدام هذا النبات كمؤشر حيوي للتلوث بهذه العناصر المعدنية الثقيلة، حيث تراوح تركيز الكادميوم في الأوراق والساق بين (0.231- 6.278ppm) ،وتركيز الرصاص بين 1.057-47.592ppm)) والنحاس بين (1.022-45.771ppm)، في حين بقي تركيز كل من الزنك والحديد ضمن الحدود الطبيعية المسموح بها.The aim of this study was to determine the trace of some heavy metals elements pb, Cd, Cu, Zn & Fe in the leaves and periderm of the Avundodonax L. using Atomic absorption spectroscopy. The samples were collected from twenty locations and divided into four groups according to traffic and human activities.The results showed an excess in the concentration of lead, cadmium and copper in the leaves and periderm of the Avundodonax L., which enables the use of this plant as a vital indicator for the pollution by these heavy metals. The concentration of cadmium in the leaves and periderm ranged between (0.231- 6.278ppm) and for lead between(1.057- 47.592ppm) and copper between(1.022 -45.771ppm). While the concentration of both zinc and iron remained within the permissible natural limits.